The Existentialist Contradiction in David Foster Wallace: How Wallace’s Sociology Illuminates the Contradiction in Wallace’s Ethics - Paolo Pitari (European Journal of American Studies)
This essay argues that Wallace’s non-fiction presents a sociology that constitutes the foundation of Wallace’s literary project. By tracing the influences of Wallace’s sociology and by contrasting Wallace’s non-fictional works with those of Zygmunt Bauman, Ulrich Beck, Anthony Giddens and Christopher Lasch, this essay provides a necessary contribution to an adequate critique of the foundation of Wallace’s literary ethics. Finally, the analysis proposes that an existentialist contradiction pervades Wallace’s work. This contradiction revolves around the problem of free will, and it characterizes a particularly strong wave of contemporary western ethics.